The Effect of Organizational Control and Structure Systems on Employee Performance at The Community And Village Empowerment Services and National and Political Unity In Banjar City - Sahudi Sahudi; Benyamin Harits; Iwan Satibi (Doctoral Program of Social Science Pasundan University, 2022)
This research starts from the fundamental problems of low performance of employees at the Agency of Empowerment of Community and Village, Nation Unity and Politics at City of Banjar. Its thought to have been came by Controling System and Organizational Structuring towards Employee Performance at the Agency of Empowerment of Community and Village, Nation Unity and Politics at City of Banjar, not yet implemented. The approach in this study refers to the context of the theory of Controling System and Organizational Structuring also Employee Performance as part of the scope of Public Administration. The method of research used explanatory survey with technical analysis Structural Equation Modeling (SEM), while the population is Agency of Empowerment of Community and Village, Nation Unity and Politics at City of Banjar. The results of the study showed the need for further research on the optimization of the increasing influence of Controling System and Organizational Structuring on Employee Performance at the Agency of Empowerment of Community and Village, Nation Unity and Politics at City of Banjar, viewed from the perspective of Public Administration. This is indicated by the existence of other variables that influence the Employee Performance at the Agency of Empowerment of Community and Village, Nation Unity and Politics at City of Banjar.